Optimization of Wear Behavior in Al-6061-B\(_4\)C Composites Using Taguchi Technique and Response Surface Analysis - Manjunatha, B.; Niranjan, H. B.; Raghavendra, S.; Satyanarayana, K. G. (Current Innovations in Chemical and Materials Sciences Vol. 9, 2024)
Metal Matrix Composites (MMCs) have been widely investigated and used in automobile and aerospace industries due to their advantages of improved strength, stiffness and increased wear resistance over monolithic alloys. Also considering limited reports on the study of weight % influence on wear characteristics of Al-6061-Boron Carbide (B4Cp) composites. This study presents the effect of weight % of B4Cp in Al-6061 alloy matrix on wear loss during dry sliding wear in pin-on-disc tribometer at different wear parameters against oil-hardened non-shrinking (OHNS) steel disk at room temperature. The composites are prepared by the stir casting technique. Taguchi is a statistical tool for acquiring data in a controlled way and is used to analyze the influence of process variables through the design of experimentation. Tribological investigations were examined according to the L9 orthogonal array of Taguchi. The influence of % of reinforcement along with load, speed and distance were examined for the wear loss of composites. The results, analysed using Taguchi and Response Surface Method to understand the significance of considered parameters (percentage of reinforcement, speed, time and load) on wear loss, revealed increased wear resistance of composite with increasing B4C particles. The observed results have been explained based on the microstructural behaviour and response surface of wear-tested composites. The study concludes that it is possible to prepare Al 6061-B4C composites using the stir casting technique, which exhibits improved hardness, wear resistance, and tensile strength with increasing reinforcement content.